Menanamkan Kemandirian Anak Usia Dini Melalui Kegiatan Practical Life - Shirley, Alifia; Romadhon , Fadilatur; Septianingrum , Ika (STKIP PGRI Ponorogo Press, 2025)
Cultivating children's independence is the responsibility of teachers at school and parents at home. Children's independence is increasingly visible by being supported by practical life activities to equip children's life skills. The purpose of the research is to find out and train the practical life of early childhood group B at RA Bahrul Ulum Pelemwatu. The research method used a qualitative method with a descriptive approach. The research subjects were 33 students of group B Raudlatul Athfal Bahrul Ulum Palemwatu. The research was conducted for two days on August 29-30, 2024, using participant observation techniques, interviews with class B teachers, and documentation. The results of the study illustrate that early childhood independence is increasing with practical life activities at school. Early childhood is able to express themselves along with the teacher providing life skills through the practice of washing socks. Children are trained by learning daily activities to dry socks, and children are increasingly trained with activities before going to school by wearing their own socks. Early childhood independence is the behavior of children's way of life given through life skills exercises to wash socks, dry socks, and use socks independently, as well as light activities related to activities both at school, at home, and in the child's play environment as practical life activities.